Analisis Pemanfaatan Laboratorium oleh Mahasiswa Kebidanan Berdasarkan Frekuensi, Intensitas, dan Pola Kunjungan untuk Mendukung Keterampilan Klinis - Roganda Simanjuntak; Novila Hardiana Utami; Noni Fidya Ayu Anandasari (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Student visit data are one of the important indicators for evaluating the utilization of educational laboratory facilities in achieving students’ practical skill competencies and professional readiness. The purpose of this study is to analyze the pattern, distribution, and trend of student visits without providing intervention or treatment in the laboratory of the Jayapura midwifery department. This study is a quantitative study with a descriptive design, using secondary data in the form of the number of laboratory visits obtained from routine reports. Research location: The study was conducted at the Laboratory of the Midwifery Department, Poltekkes Kemenkes Jayapura, Research time: Secondary data analysis includes student visits during 2023, 2024, and 2025. Data were analyzed retrospectively to see the trend and distribution of visits over the past three years with the Kruskal–Wallis test. The results of the research from the Graph of student visit trends to the Laboratory of the Midwifery Department in 2023–2025 show fluctuations in the number of visits with a relatively consistent seasonal pattern every year. There is a significant difference in the number of student visits to the laboratory between 2023, 2024, and 2025. The test results show a Chi-Square value of 8.742 with a degree of freedom (df) of 2 and a significance value (p) of 0.013. Because the p-value was less than 0.05, instead indicates a statistically significant difference in laboratory utiliztion patterns.  The laboratory functions as a learning facility whose use follows curriculum needs therefore, scheduling, resource management and facility readiness need to be adjusted to peak periods of academic activity.